2017
DOI: 10.1111/dech.12286
|View full text |Cite
|
Sign up to set email alerts
|

A Moral Economy of Water: Charity Wells in Egypt's Nile Delta

Abstract: Though commonly viewed as a human right, access to water is often difficult and highly unequal within and between communities, depending on various social and power relations, access mechanisms and property rights regimes. However, moral norms and subsistence ethics can also play a balancing role, enhancing access to water for vulnerable groups and individuals, particularly in contexts of water scarcity. Using the example of a Nile Delta village, this article explores the role of charitable water wells (sobol)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…Moral economies produce norms that govern how resources should be exchanged and may be understood to uphold a human right to water. Recent studies have explored how the moral economy concept animates water-related altruism and exchanges in Egypt (ElDidi & Corbera, 2017), Italy (Fantini, 2014), and the United States (Arnold, 2017). Research on inter-household water sharing in Bolivia has also indicated that a moral economy of water underlies reciprocal obligations to share water and moral commitments to survival and subsistence (Wutich, 2011, p. 20).…”
Section: Section 2: Cross-cutting Factors That Shape Water Sharingmentioning
confidence: 99%
“…Moral economies produce norms that govern how resources should be exchanged and may be understood to uphold a human right to water. Recent studies have explored how the moral economy concept animates water-related altruism and exchanges in Egypt (ElDidi & Corbera, 2017), Italy (Fantini, 2014), and the United States (Arnold, 2017). Research on inter-household water sharing in Bolivia has also indicated that a moral economy of water underlies reciprocal obligations to share water and moral commitments to survival and subsistence (Wutich, 2011, p. 20).…”
Section: Section 2: Cross-cutting Factors That Shape Water Sharingmentioning
confidence: 99%
“…Water insecurity has consequences for physical (Geere, Hunter, & Jagals, 2010;Prüss-Ustün et al, 2014) and mental health (Aihara, Shrestha, Kazama, & Nishida, 2015;W. Jepson, 2014;Stevenson et al, 2012;Workman & Ureksoy, 2017;Wutich & Ragsdale, 2008), interpersonal and community relations (El Didi & Corbera, 2017;Mason, 2014;Wutich, 2011), and daily routines (Sultana, 2009). Water insecurity is expected to worsen due to climate change, increased global water use, and inequalities in water distribution (Cook & Bakker, 2012;Department of Defense, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Perkembangan teknologi ini rasanya menjadikan praktek filantropi dalam Islam--yang umumnya dipahami sebagai aktivitas memberi secara sukarela dan membantu individu lain yang sedang kesulitan--bisa bertansformasi menjadi filantropi ideal sebagaimana yang dibayangkan oleh banyak kalangan (ElDidi and Corbera 2017;Fauzia 2017;O'Brien 2015). Bentuk filantropi ideal tersebut, mengacu pada definisi Robert Payton (Payton and Moody 2008), dapat dijelaskan sebagai perbuatan sukarela untuk kemashalatan umum.…”
Section: B Revolusi Industri 40 Islam Digital Dan Filantropi Islamunclassified